2005
DOI: 10.4319/lo.2005.50.1.0246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface roughness and oscillatory flow on the dissolution of plaster forms: Evidence for nutrient mass transfer to coral reef communities

Abstract: We dissolved plaster forms in seawater to examine the effects of surface roughness and flow conditions on masstransfer rates. Plaster blocks with varying roughness were dissolved under both steady and oscillatory flows between 7 and 43 cm s Ϫ1 yielding calcium mass-transfer coefficients (S Ca ) that varied from 0.5 to 3 m d Ϫ1. S Ca measured in a flume was 30-40% greater under oscillatory flow than under steady flow at flow speeds Ͻ10 cm s Ϫ1 ; this difference decreased with increasing flow speed. Plaster bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
62
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 24 publications
(46 reference statements)
4
62
1
Order By: Relevance
“…where MW gyp is the molecular weight of gypsum (172.2 g mol 21 ), Dt is the time taken to dissolve the form, A f is the surface area of the form, and DC is the concentration difference across the boundary layer (20.8 mol m 23 ; Falter et al 2005). For cylinders, A f was calculated on the basis of the average height and diameter of the cylinders measured before and after being dissolved.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…where MW gyp is the molecular weight of gypsum (172.2 g mol 21 ), Dt is the time taken to dissolve the form, A f is the surface area of the form, and DC is the concentration difference across the boundary layer (20.8 mol m 23 ; Falter et al 2005). For cylinders, A f was calculated on the basis of the average height and diameter of the cylinders measured before and after being dissolved.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient uptake is considered mass-transfer limited when the concentration at the surface (C s ) is very small in comparison to the concentration in the bulk fluid (C s ,, C b ), and thus, S R b (Eq. 1) The correlations proposed by Bilger and Atkinson (1992) have been shown to be effective in predicting rates of nutrient mass transfer to both experimental (Atkinson and Bilger 1992;Thomas and Atkinson 1997) and naturally occurring (Falter et al 2004) coral reef communities. Falter et al (2004) showed that given the range of flows and roughness heights found for most reef communities, and the values of Sc for dissolved metabolites (.400), these heat and mass transfer correlations could be simplified into the following relationship:…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The mass transfer of these solutes is a complex process, and aside from diffusion, the transport of solutes to and from the water column and organisms is affected by water velocity, solute concentration, chemical reactions, and the geometry of the organism (Riebesell et al 1993;Larned et al 2004;Falter et al 2005). Hence, the ecophysiology of aquatic organisms is directly influenced by the surrounding environment and the rates of mass transfer have a profound influence on processes such as photosynthesis, respiration, and nutrient uptake (Ploug et al 1999(Ploug et al , 1999(Ploug et al , 2002.…”
mentioning
confidence: 99%